Five new species, two new sexual morph reports, and one new geographical record of Apiospora (Amphisphaeriales, Sordariomycetes) isolated from bamboo in Yunnan, China - Han, Li-Su; Liu, Chao; Dai, Dong-Qin; Promputtha, Itthayakorn; Elgorban, Abdallah M.; Al-Rejaie, Salim; Li, Qiang; Wijayawardene, Nalin N. (Frontiers in Cellular and Infection Microbiology, 2024)
Apiospora is an important genus in the Apiosporaceae family with a worldwide distribution. They exhibit different lifestyles including pathogenic, saprophytic, and endophytic. In this study, we aimed to explore the Apiospora associated with bamboo and collected 14 apiospora-like taxa from the forests of Yunnan Province, China. Morphological and phylogenetic analyses (combined ITS, LSU, tef1-α, and tub2 sequence data) confirmed that these collections belong to Apiospora s. str. and reports five new species (viz., Ap. dehongensis, Ap. jinghongensis, Ap. shangrilaensis, Ap. zhaotongensis, and Ap. zhenxiongensis). New sexual morphs of asexually typified Ap. globose and Ap. guangdongensis species, and a new geographical record of Ap. subglobosa are also reported. The findings of this study not only enhance the diversity of bambusicolous fungi in the region of Yunnan, but also geographical distribution of some known Apiospora species.